Searching for information on the web: A guideline for effective searching - Mat Yamin, Fadhilah; Ramayah, T. (IGI Global, 2012)
To date, the World Wide Web (WWW) is the most popular environment for information searching and retrieval. One of the steps in searching for information on the web is by entering a query to the search system and reformulating the queries. There are many challenges and issues in formulating effective queries. Effective queries will produce relevant document that matches the user information need. The discussion of this chapter will be focusing on how to apply both breadth and depth search query formulation strategies for effective searching on the web. The discussion will be based on a selected search task. At the end of the chapter, a recommendation for a step-by-step searching procedure will be presented as a guideline for effective searching.